Rhythm and temporality: a phenomenological examination of music performance - Boast, Philip James (2018)
This thesis applies a phenomenological approach to music performance. Drawing on Christopher Hasty’s interpretation of musical metre as ‘projection’, I examine the constitutive basis for the shared sense of time that underpins ensemble performance. The research considers a musician’s sensitivity to pulse and tempo and the capacity to time instrumental actions. I argue that a performer's relationship with musical time can be meaningfully articulated in the terms of Edmund Husserl’s structure of internal time-consciousness. The aims of the thesis are achieved by bringing together musicological and phenomenological perspectives and through conducting two phenomenologically-informed studies of the experience of music performance. A preliminary study involves a self-reflective examination of the performance of an instrumental skill. In the primary study, I undertake and analyse interviews with nine working musicians who perform in contemporary popular music. My principal findings are that musicianship requires an autonomous sense of musical pulse, that the determination and maintenance of tempo is best served through a bodily awareness of time and that the performance of rhythm involves the articulation of cyclic patterns of ‘horizontal’ and ‘vertical’ movement. Further, the intersubjective performance of groove involves an empathic awareness characterised by an experiential sense of ‘connecting’, or ‘locking-in’. An unanticipated finding is that a critical ability is to maintain an appropriate and focussed awareness within a complex and dynamic situation. I conclude that from a phenomenological perspective: Hasty’s projection of metre is founded in time-constitution; the instrumental expression of rhythm arises through a temporalising, bodily consciousness, and is structured through the ongoing projection of a metric framework; the ability of a musician to act in synchrony with others is founded in a co-projection of metre within a co-constitution of ‘world-time’; and to focus attention is to modulate the anticipative sense of an unfolding activity.